The Comparison of Uric Acid Levels in Incentive and Advanced Phase Tuberculosis Patients at the Kupang Timur District Health Center - Novian Agni Yudhaswara; Meilanisa Saebessi; Pius Kopong Tokan (Poltekkes Kemenkes Kupang, 2025)
Tuberculosis is a direct infectious disease caused by TB germs (Mycobacterium tuberculosis). Data from the 2021 Kupang District Health Office noted that the number of TB cases at the Oesao health center in 2021 was 41 cases, then in 2022 the Naibonat Health Center reported that the total number of tuberculosis patients reached 69 cases. TB treatment is carried out in 2 stages, namely in the intensive phase (2 months) and followed by the continuation phase (4 months) with Anti Tuberculosis Drugs. Joint pain is one of the side effects of OAT, which is a result of pyrazinamide and ethambutol which can cause excessive reabsorption of uric acid, causing hyperuricemia. The purpose of this study was to compare uric acid levels in tuberculosis patients during the intensive and advanced phases of treatment at the East Kupang District Health Center. This research is a type of quantitative research with a comparative design. The population in this study were patients with tuberculosis in the intensive and advanced phase at the East Kupang District Health Center. And the samples obtained in this study were 51 capillary blood samples from patients with tuberculosis in the intensive and advanced phases, then examinations were carried out in March-April 2023 using the Point Of Care Testing (POCT) method. Analysis of the results of this study using t-test 2 free samples. Based on the results of the research conducted, there was a significant average difference, namely uric acid levels in tuberculosis patients who were taking OAT, uric acid levels in intensive phase tuberculosis patients were higher than uric acid levels during the advanced phase.